Vampire leaders suck : the dark forces draining academic institutions - Jones, Patrice W. Glenn (Emerald Publishing Limited, 2025)
Vampire Leaders Suck sheds light on the characteristics and impacts of a form of toxic leadership that sucks the life out of individuals, groups, and organizations. Using vampire lore allegory, leader experiences, and critical examination, it book equips readers with the knowledge and tools to identify, understand, and counteract these detrimental behaviors. This book aims to unveil the mystic of vampirism as a precursor to fostering a culture of positive leadership by contrasting vampire-like qualities with strategies for nurturing supportive, inspiring, and ethical leadership. Though the content of this book plays out in higher education, the relatability makes the content a valuable resource for educators, administrators, HR professionals, and policy makers.